Charles Darwin and John Herschel - B. Warner (South African Journal of Science)
The influence of John Herschel on the philosophical thoughts of Charles Darwin, both through the former's book, Natural Philosophy, and through their meeting in 1836 at the Cape of Good Hope, is discussed. With Herschel having himself speculated on evolution just a few months before he met Darwin, it is probable that he stimulated at least the beginnings of the latter's lifelong work on the subject.